Towards voluntary tax compliance: Understanding the impact of altruistic and egocentric orientation / Susan Hydra Sikayu … [et al.] - Sikayu, Susan Hydra; Gabriel Puem, Lucy Batchy; Jonathan, Lulu; Enggong, Tina Stephen (Universiti Teknologi Mara Selangor, 2020)
Tax is one of the main sources of revenue for a country. Therefore, a sustainable contribution of tax revenue is crucial for a nation to prosper. Yet, the conundrum as to why taxpayers comply voluntarily, while, others resent from paying taxes is still unresolved. Hitherto, the conventional economic deterrent approach has failed to clearly explain this gap. Hence, the social psychology approach is explored in examining the taxpayers’ attitude. This study evaluates the taxpayers’ altruistic and egocentric oriented attitudes. Herein, these attitudes were examined for their corresponding relationship with taxpayers’ voluntary compliance. Survey questionnaires were distributed to the individual taxpayers of Malaysia using convenience sampling. Subsequently, 244 useable questionnaires were analyzed using SPSS and Smart PLS 3. The results revealed that the altruistic group was significantly happier and had a better attitude towards tax compliance. More importantly, altruistic orientation was significantly associated with taxpayers’ compliance. These findings highlighted the importance of imparting altruistic prosocial value within the education system and the society at large, in nurturing voluntary tax compliance.